Characterisation of melicope ptelefolia bioactivities antioxidant, anticancer, anticadmium-induced cytotoxicity and microarray transcriptome profiling / Mohammad Faujul Kabir - Mohammad Faujul, Kabir (2019)
Melicope ptelefolia (MP), a well-known herb in a number of Asian countries, has been used as a traditional medicine. However, not many studies have been currently done to evaluate its medicinal benefits. The present study reports antioxidant, anticancer, anticadmium-induced cytotoxicity and gene expression modulating activities of MP leaf extracts. MP leaves were dried, powdered and extracted sequentially using hexane (HX), ethyl acetate (EA), methanol (MeOH) and water (W). Antioxidant activity was evaluated through chemical and cellular antioxidant activity (CAA) assays. Antiproliferative activity against HCT116, HepG2, HCC1937 and MDA-MB-231 cancer cell lines was evaluated through cell viability, apoptosis and cell cycle assays. The cytoprotective effect of MP extracts on Hs27 cells exposed to CdCl2 was evaluated using cell viability assay. Microarray gene expression profiling was done using GeneChip™ Human Gene 2.0 ST Array. The transcriptome data was analysed using Expression Console, Transcriptome Analysis Console and Ingenuity Pathway Analysis (IPA) softwares, along with GATHER, PANTHER and STRING bioinformatics web tools. Microarray data was validated by profiling the expression of selected genes through quantitative reverse transcription PCR (RT-qPCR). Based on the chemical antioxidant assays, MP-HX exhibited the highest antioxidant potential. The CAA assay revealed that MP-HX had a lower EC50 value of 11.30 ± 0.68 µg/mL, compared to MPEA, which was 37.32 ± 0.68 µg/mL. MP-HX and MP-EA demonstrated cytotoxic effect on all four cancer cell lines tested. MP-HX showed the most notable antiproliferative activity against MDA-MB-231 (IC50 = 57.81 ± 3.49 µg/mL) and HCT116 (IC50 = 58.04 ± 0.96 µg/mL). MP-EA showed the strongest antiproliferative activity against HCT116 (IC50 = 64.69 ± 0.72 µg/mL). MP-HX and MP-EA were able to induce caspasedependent apoptotic cell death in the four cancer cell lines tested and they altered the cell cycle distribution in most of the cancer cell lines. Gene expression study in HCT116 and HepG2 cells indicated that MP-HX induced differential expression of 1290 and 1325 genes, respectively (microarray fold change ≥ ±2.0). In both cell lines, MP-HX modulated the expression of many genes in directions that support antiproliferative activity. MP-HX upregulated the expression of pro-apoptotic, cell cycle arresting and metastasis suppression genes, while it also downregulated the expression of anti-apoptotic, cell cycle and tumor promoting genes. MP-HX and MP-EA treatments in Hs27 cells resulted to the upregulation of numerous antioxidant and cell cycle promoting genes, including genes that play vital roles in wound healing and aging processes. Bioinformatics data analysis revealed that MP-HX and MP-EA modulated canonical pathways and activated several upstream regulators associated with wound healing process in Hs27 cells. In Hs27 exposed to CdCl2, the percentage of cell viability was increased in the presence of MP-HX or MP-EA pretreatments, suggesting cytoprotective effect of MP extracts. Microarray profiling of Hs27 cells exposed to CdCl2 demonstrated modulation of apoptosis and heat shock protein genes expression when the cells were pretreated with MP extracts. This observation provided insights on the extracts cytoprotective mechanisms. The findings of the present study project the potential value of MP in nutraceutical and pharmaceutical industries.